Pengaruh Media Linimasa Terhadap Hasil Belajar PAI Siswa di SDN 1 Cipinang Kecamatan Beber Kabupaten Cirebon - Casta, Casta; Abas, Saehu; Mukaromah, Omah (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2023)
This study is taken from the problem of the Covid-19 pandemic where all learning activities are diverted to online learning so that in the process there are several obstacles, especially to determine the influence of Whatsapp-based timeline media on PAI learning outcomes.This study aims to determine how well the use of Whatsapp-based timeline media on the learning outcomes of PAI 6th grade students in SDN 1 Cipinang, knowing the learning outcomes of PAI 6th grade students in the application of Whatsapp-based timeline media in SDN 1 Cipinang, and to determine the influence of Whatsapp-based timeline media on the learning outcomes of PAI 6th grade students in SDN 1 Cipinang.This study uses quantitative research method approach with ex-post facto research type, associative causality research design. Data collection using questionnaires given to a sample of 25 students using the validity and reliability of instruments, descriptive, classical assumption Test, simple regression analysis, and hypothesis.The results showed that the media learning timeline based on Whatsapp in SDN 1 Cipinang obtained a percentage value of 78.92% which means it belongs to the category of good. The learning outcomes of 6th grade students at SDN 1 Cipinang, obtained a percentage value of 79.04% which means it belongs to the category of good. The results of the hypothesis test concluded that there is a significant influence of Whatsapp-based timeline media on student learning outcomes indicated by the value of the coefficient thitung 3.121 > ttable, 1.713, then Ho is rejected and Ha is accepted which means there is a significant influence between Whatsapp-based timeline media on student learning outcomes. In conclusion, the use of Whatsapp timeline media has succeeded in improving the learning outcomes of PAI 6th grade students at SDN 1 Cipinang in online learning in the Covid-19 era.Keyword: Timeline Media; Whatsapp Media; Learning Outcomes. Abstrak Penelitian ini diambil dari adanya masalah pandemi Covid-19 dimana seluruh aktivitas belajar dialihkan pada pembelajaran daring sehingga dalam prosesnya mengalami beberapa hambatan terutama untuk mengetahui pengaruh media linimasa berbasis Whatsapp terhadap hasil belajar PAI.Penelitian ini betujuan untuk mengetahui seberapa baik penggunaan media linimasa berbasis Whatsapp terhadap hasil belajar PAI siswa kelas VI di SDN 1 Cipinang, mengetahui hasil belajar pada mata pelajaran PAI siswa kelas VI dalam penerapan media linimasa berbasis Whatsapp di SDN 1 Cipinang, dan untuk mengetahui pengaruh media linimasa berbasis Whatsapp terhadap hasil belajar PAI siswa kelas VI di SDN 1 Cipinang.Penelitian ini menggunakan pendekatan metode penelitian kuantitatif dengan jenis penelitian ex-post facto, desain penelitian asosiatif kausalitas. Pengumpulan datanya menggunakan angket yang diberikan kepada sampel sebanyak 25 siswa dengan menggunakan uji validitas dan reliabilitas instrumen, deskriptif, uji asumsi klasik, analisis regresi sederhana, dan hipotesis.Hasil penelitian menunjukkan bahwa media belajar linimasa berbasis Whatsapp di SDN 1 Cipinang didapat nilai persentase sebesar 78,92% yang berarti termasuk kategori Baik. Hasil belajar siswa kelas VI di SDN 1 Cipinang, didapat nilai persentase sebesar 79,04% yang berarti termasuk kategori Baik. Hasil uji hipotesis diperoleh kesimpulan terdapat pengaruh yang Signifikan dari media linimasa berbasis Whatsapp terhadap hasil belajar siswa ditunjukkan dengan nilai koefisien thitung 3,121 > ttabel, 1,713, maka H0 ditolak dan Ha diterima yang berarti terdapat pengaruh yang Signifikan antara media linimasa berbasis Whatsapp terhadap hasil belajar siswa. Kesimpulannya penggunaan media linimasa Whatsapp berhasil meningkatkan hasil belajar PAI siswa kelas IV di SDN 1 Cipinang pada pembelajaran daring di era Covid-19.Kata Kunci: Media Linimasa; Media Whatsapp; Hasil Belajar.